Implications of insecticide resistance for malaria vector control with long-lasting insecticidal nets: a WHO-coordinated, prospective, international, observational cohort study. Issue 6 (June 2018) - Kleinschmidt, Immo; Bradley, John; Knox, Tessa Bellamy; Mnzava, Abraham Peter; Kafy, Hmooda Toto; Mbogo, Charles; Ismail, Bashir Adam; Bigoga, Jude D; Adechoubou, Alioun; Raghavendra, Kamaraju; Cook, Jackie; Malik, Elfatih M; et al.
Summary: Background: Scale-up of insecticide-based interventions has averted more than 500 million malaria cases since 2000. Increasing insecticide resistance could herald a rebound in disease and mortality. We aimed to investigate whether insecticide resistance was associated with loss of effectiveness of long-lasting insecticidal nets and increased malaria disease burden. Methods: This WHO-coordinated, prospective, observational cohort study was done at 279 clusters (villages or groups of villages in which phenotypic resistance was measurable) in Benin, Cameroon, India, Kenya, and Sudan. Pyrethroid long-lasting insecticidal nets were the principal form of malaria vector control in all study areas; in Sudan this approach was supplemented by indoor residual spraying. Cohorts of children from randomly selected households in each cluster were recruited and followed up by community health workers to measure incidence of clinical malaria and prevalence of infection. Mosquitoes were assessed for susceptibility to pyrethroids using the standard WHO bioassay test. Country-specific results were combined using meta-analysis. Findings: Between June 2, 2012, and Nov 4, 2016, 40 000 children were enrolled and assessed for clinical incidence during 1·4 million follow-up visits. 80 000 mosquitoes were assessed for insecticide resistance. Long-lasting insecticidal net users had lower infection prevalence (adjusted odds ratio [OR] 0·63, 95% CI 0·51–0·78) and disease incidence (adjusted rate ratio [RR] 0·62, 0·41–0·94) than did non-users across a range of resistance levels. We found no evidence of an association between insecticide resistance and infection prevalence (adjusted OR 0·86, 0·70–1·06) or incidence (adjusted RR 0·89, 0·72–1·10). Users of nets, although significantly better protected than non-users, were nevertheless subject to high malaria infection risk (ranging from an average incidence in net users of 0·023, [95% CI 0·016–0·033] per person-year in India, to 0·80 [0·65–0·97] per person year in Kenya; and an average infection prevalence in net users of 0·8% [0·5–1·3] in India to an average infection prevalence of 50·8% [43·4–58·2] in Benin). Interpretation: Irrespective of resistance, populations in malaria endemic areas should continue to use long-lasting insecticidal nets to reduce their risk of infection. As nets provide only partial protection, the development of additional vector control tools should be prioritised to reduce the unacceptably high malaria burden. Funding: Bill & Melinda Gates Foundation, UK Medical Research Council, and UK Department for International Development .